Effect of ouabain on calcium signaling in rodent brain: A systematic review of in vitro studies - Leite, Jacqueline Alves; Pôças, Elisa; Maia, Gisele Silva; Barbosa, Leandro; Quintas, Luis Eduardo M.; Kawamoto, Elisa Mitiko; Silva, Maria Luiza Correia da; Scavone, Cristoforo; de Carvalho, Luciana E. Drumond (Frontiers in Pharmacology, 2022)
The Na+/K+-ATPase is an integral membrane ion pump, essential to maintaining osmotic balance in cells in the presence of cardiotonic steroids; more specifically, ouabain can be an endogenous modulator of the Na+/K+-ATPase. Here, we conducted a systematic review of the in vitro effects of cardiotonic steroids on Ca2+ in the brain of rats and mice. Methods: The review was carried out using the PubMed, Virtual Health Library, and EMBASE databases (between 12 June, 2020 and 30 June, 2020) and followed the guidelines described in the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA). Results: in total, 829 references were identified in the electronic databases; however, only 20 articles were considered, on the basis of the inclusion criteria. The studies demonstrated the effects of ouabain on Ca2+ signaling in synaptosomes, brain slices, and cultures of rat and mouse cells. In addition to the well-known cytotoxic effects of high doses of ouabain, resulting from indirect stimulation of the reverse mode of the Na+/Ca2+ exchanger and increased intracellular Ca2+, other effects have been reported. Ouabain-mediated Ca2+ signaling was able to act increasing cholinergic, noradrenergic and glutamatergic neurotransmission. Furthermore, ouabain significantly increased intracellular signaling molecules such as InsPs, IP3 and cAMP. Moreover treatment with low doses of ouabain stimulated myelin basic protein synthesis. Ouabain-induced intracellular Ca2+ increase may promote the activation of important cell signaling pathways involved in cellular homeostasis and function. Thus, the study of the application of ouabain in low doses being promising for application in neurological diseases.